2017
DOI: 10.1371/journal.pone.0180759
|View full text |Cite
|
Sign up to set email alerts
|

The impact of access to immunization information on vaccine acceptance in three countries

Abstract: IntroductionVaccine acceptance is a critical component of sustainable immunization programs, yet rates of vaccine hesitancy are rising. Increased access to misinformation through media and anti-vaccine advocacy is an important contributor to hesitancy in the United States and other high-income nations with robust immunization programs. Little is known about the content and effect of information sources on attitudes toward vaccination in settings with rapidly changing or unstable immunization programs.Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
3
36
1
2
Order By: Relevance
“…Participants were also reluctant to receive HPV vaccination considering the weaknesses of the macro-healthcare system and problematic doctor–patient relationship, which in turn affected their decision-making process. A recent study [23] investigated factors influencing vaccine acceptance in Botswana, the Dominican Republic, and Greece and reported that the operation of the public and private healthcare potentially leads to (dis) trust regarding vaccines among people. This finding concurs with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also reluctant to receive HPV vaccination considering the weaknesses of the macro-healthcare system and problematic doctor–patient relationship, which in turn affected their decision-making process. A recent study [23] investigated factors influencing vaccine acceptance in Botswana, the Dominican Republic, and Greece and reported that the operation of the public and private healthcare potentially leads to (dis) trust regarding vaccines among people. This finding concurs with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Attitudes also played a significant factor; in one three-country study of maternal vaccine acceptance, maternal attitudes toward the government and trust in the healthcare system was shown to influence vaccine uptake. 30 The parallels between a mother choosing to vaccinate her child versus choosing to vaccinate her child in utero highlight the importance of understanding this as a factor for uptake.…”
Section: Considering Maternal Vaccine Knowledge Attitudes and Beliefsmentioning
confidence: 99%
“…The study adopted the Andersen and Newman Behavioural Model [ 23 ] for health service utilization to permit systematic identification of factors that influence individual decisions, the environmental and need factors for vaccine acceptance. This was then modified it using Handy et al 2017 [ 24 ] for interrelationships that drive vaccine acceptance. In order to understand vaccine acceptance, there is need to explore the underlying factors at various levels.…”
Section: Introductionmentioning
confidence: 99%